Myo-inositol effects in women with PCOS: a meta-analysis of randomized controlled trials - Unfer, Vittorio; Facchinetti, Fabio; Orrù, Beatrice; Giordani, Barbara; Nestler, John (Endocrine Connections, 2017)
Myo-inositol (MI) supplementation in women with polycystic ovary syndrome (PCOS) has been evaluated over the last years. Many hormonal and reproductive impairments associated with this disorder seem relieved by the supplement. The objective of the meta-analysis was to assess the effects of MI alone or combined with d-chiro-inositol (DCI) on the endocrine and metabolic abnormalities of women with PCOS. Literature was retrieved from selected databases, MEDLINE, EMBASE, PubMed and Research Gate (up to November 2016). Only randomized controlled trials (RCTs) investigating the effects of MI alone or combined with DCI were reviewed. Nine RCTs involving 247 cases and 249 controls were included. Significant decreases in fasting insulin (SMD = −1.021 µU/mL, 95% CI: −1.791 to −0.251, P = 0.009) and homeostasis model assessment (HOMA) index (SMD = −0.585, 95% CI: −1.145 to −0.025, P = 0.041) were identified after MI supplementation. The trial sequential analysis of insulin meta-analysis illustrates that the cumulative z-curve crossed the monitoring boundary, providing firm evidence of the intervention effect. A slight trend toward a reduction of testosterone concentration by MI with respect to controls was found (SMD = −0.49, 95% CI: −1.072 to 0.092, P = 0.099), whereas androstenedione levels remained unaffected. Throughout a subgroup’s meta-analysis, a significant increase in serum SHBG was observed only in those studies where MI was administered for at least 24 weeks (SMD = 0.425 nmol/L, 95% CI: 0.050–0.801, P = 0.026). These results highlight the beneficial effect of MI in improving the metabolic profile of women with PCOS, concomitantly reducing their hyperandrogenism.